2011
DOI: 10.1093/ndt/gfr143
|View full text |Cite
|
Sign up to set email alerts
|

Home blood pressure (BP) monitoring in kidney transplant recipients is more adequate to monitor BP than office BP

Abstract: We conclude that the results obtained with HBPM were closer to the ABPM results than those obtained with BP obtained at oBP, being more sensitive to detect poor control of hypertension in renal transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 24 publications
4
23
1
1
Order By: Relevance
“…The use of standardized techniques, as used in clinical trials of hypertension with .1 measurement of BP, can provide improved concordance rates between CBP and ABPM as seen in a study by Haydar et al 19 Other researchers have demonstrated that HBPM determinations had a significantly better agreement with ABPM than CBP (72% versus 54%) even though both the CBP and the HBPM correlated with ABPM. 20 The use of ABPM is being recommended more broadly in the general population 21 to better assess the clinical importance of nocturnal hypertension, masked hypertension, and white-coat hypertension on the risk for vascular events. Patients with high-normal or normal CBP with asymptomatic target organ damage or high CV risk should undergo ABPM for possible masked hypertension.…”
Section: Diagnosis Of Hypertensionmentioning
confidence: 99%
“…The use of standardized techniques, as used in clinical trials of hypertension with .1 measurement of BP, can provide improved concordance rates between CBP and ABPM as seen in a study by Haydar et al 19 Other researchers have demonstrated that HBPM determinations had a significantly better agreement with ABPM than CBP (72% versus 54%) even though both the CBP and the HBPM correlated with ABPM. 20 The use of ABPM is being recommended more broadly in the general population 21 to better assess the clinical importance of nocturnal hypertension, masked hypertension, and white-coat hypertension on the risk for vascular events. Patients with high-normal or normal CBP with asymptomatic target organ damage or high CV risk should undergo ABPM for possible masked hypertension.…”
Section: Diagnosis Of Hypertensionmentioning
confidence: 99%
“…This study have taken multiple measurements for HBPM, OBPM, and ABPM to produce the maximum reliability among the three methods of BP measurements as in other studies[3467] in literature, where the measurements have been few. We have used ABPM as a “gold standard”[13] for comparing with HBPM using the average daytime BP for comparison as in another report by Agena et al [6] With HBPM, there is no consensus regarding the frequency of readings or the days needed for observation.…”
Section: Discussionmentioning
confidence: 99%
“…We have used ABPM as a “gold standard”[13] for comparing with HBPM using the average daytime BP for comparison as in another report by Agena et al [6] With HBPM, there is no consensus regarding the frequency of readings or the days needed for observation. Studies are based on reproducibility and consistency of BP with HBPM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor control not only has detrimental CV effects for the recipient but also is an independent risk factor for graft failure [55]. Agena et al [56 ]found that HBPM correlated better with ABPM than with OBPM in kidney recipients between 1 and 10 years after transplantation. More study is needed to determine the prognostic value of HBPM in graft failure, CV outcomes, and its utility in the management of hypertension in this population.…”
Section: Dialysis and Transplantmentioning
confidence: 99%